Detection of Leakage Areas in an Earth Embankment from GPR Measurements and Permeability Logging - Raphaël Antoine; Cyrille Fauchard; Yannick Fargier; Edouard Durand (International Journal of Geophysics)
Ground penetrating radar (GPR) is a nondestructive method allowing the improvement of our knowledge of civil engineering structures. In particular, this method may be a nondestructive efficient tool for dike diagnosis and complete classical geotechnical methods. In this paper, we present GPR observations obtained on an earth embankment (crest and sloped paved revetment) in bad condition and located on the lateral canal of the Loire river (Saint Firmin, 80 km South East of Orléans). These measurements are combined with corings, visual inspection, and permeability logging performed with an updated drilling system, the Perméafor. This survey leads (i) to the detection of decompressed zones associated with leakage areas visible at the foot of the downstream slope and (ii) to the location of potentials voids underneath the paved revetment. This multidisciplinary approach complied with the dike inspection methodology proves its efficiency for the assessment of earth embankments.